ACADEMIC SUPERVISION: EFFORTS TO IMPROVE THE LEARNING PROCESS SKILLS OF ELEMENTARY SCHOOL TEACHERS - Farida; Ary Kiswanto Kenedi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by findings that the learning process of elementary school teachers did not align with the characteristics of effective learning. Observations revealed that teachers still relied on lesson plans downloaded from the internet, and their learning processes and assessments were not fully in accordance with curriculum demands, indicating the need for improvement. The purpose of this study was to determine the improvement of teachers’ skills in carrying out the learning process using a problem-centered learning model through academic supervision activities. This research was a school action research adapted from McTaggart and Kemmis's classroom action research design, consisting of stages of planning, implementation, observation, and reflection. The study was conducted at SDN 28 Rawang Timur, Padang, involving 10 teachers. The results showed that teachers achieved an average skill score of 88.86 in cycle I and 83.59 in cycle II, indicating an improvement in teachers’ learning process skills through academic supervision. This study suggested that scheduling supervision in agreement with teachers is necessary to optimize its implementation. The implication of this research is that it can serve as a basis for supervisors to enhance the learning process skills of elementary school teachers.